Using a mobile application to support tourist’s information and services needs: the case of Cabo Verde Islands - Adrião, Zenaida (2019)
Mobile applications are proliferating in all business domains. In the tourism sector, that is information intensive, and a global phenomenon, the development of efficient solutions for deliver information and services for “information-starving” tourists is a challenge, and opportunity but mostly a necessity of modern competitive touristic destinations. This paper briefly discusses the role that mobile devices applications have in the support of information and services of Cabo Verde visiting tourists and presents the design and development of a prototype application Android-based that enable important information and services for all Cabo Verde tourists that need to know more about Cabo Verde islands and their important information and services, manly related with their culture, gastronomy, events and hospitality services.